التعرية المائية في المنطقة الشرقية من محافظة ميسان وأثارها البيئية - شنته سعد كاظم; غليس ناهي السعيدي علي (Journal of College of Education, 2019)
This study aims to study a natural phenomenon with dangerous interferences in the eastern region of Maysan province. Which was determined from the equal altitude line (10) above the sea level, which is the eastern border of the tributaries of the Tigris River, and ending with the political border line between Iraq and Iran. And to uncover its manifestations and environmental effects. The importance of research lies in the subject of the phenomenon itself, as the phenomenon described above is one of the most important problems that stand in the way of preventing development in the region and its development despite the possibilities available 5 (such as agriculture and oil wealth, as well as the distinctive character of the region, , Which can be used for ecotourism especially in the cold season of the year. The study reviewed the environmental condition of the region in the year of the research subject, which is the most important of which are the following: - Geological structure, surface, nature of hull, soil characteristics, vegetation cover, The main findings of the research are: - Water leaks have wide inter-faceted effects, especially on roads and bridges, which are the mainstay of development and prosperity. In any area, especially the study area, and requires taking measures toخ address those when thinking about developing the area under consideration